Area calculation based on GADM geographic information system database - Adi Setiawan; Eko Sediyono (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This paper aims to provide an overview of the calculation of the area of Indonesia based on the boundaries of sub-district/village, district, regency/city. The circle approach method is proposed as a fast method for determining the land area of Indonesia. The total area of Indonesia can be obtained by adding up to 33 provinces or 502 regencies/cities or 6696 districts or 77474 sub-districts. Calculation of the area of the area using district boundaries is better used in the calculation of the area of Indonesia which is obtained 1,965,443.51 km2. The results obtained are 2.53% bigger than the reference area.